MEchanical DIlatation of the Cervix in a Scarred uterus (MEDICS): the study protocol of a randomised controlled trial comparing a single cervical catheter balloon and prostaglandin PGE2 for cervical ripening and labour induction following caesarean delivery - Arijit Biswas; Soe-Na Choo; Abhiram Kanneganti; Muhammad Nur Dinie Bin Abdul Aziz; Leta Loh; Carol Hargreaves; Vikneswaran Gopal; Yiong Huak Chan; Ida Suzani Ismail; Claudia Chi; Citra Mattar (BMJ Open)
Introduction Labour induction in women with a previous caesarean delivery currently uses vaginal prostaglandin E2 (PGE2), which carries the risks of uterine hyperstimulation and scar rupture. We aim to compare the efficacy of mechanical labour induction using a transcervically applied Foley catheter balloon (FCB) with PGE2 in affected women attempting trial of labour after caesarean (TOLAC).Methods and analysis This single-centre non-inferiority prospective, randomised, open, blinded-endpoint study conducted at an academic maternity unit in Singapore will recruit a total of 100 women with one previous uncomplicated caesarean section and no contraindications to vaginal delivery. Eligible consented participants with term singleton pregnancies and unfavourable cervical scores (≤5) requiring labour induction undergo stratified randomisation based on parity and are assigned either FCB (n=50) or PGE2 (n=50). Treatments are applied for up to 12 hours with serial monitoring of the mother and the fetus and serial assessment for improved cervical scores. If the cervix is still unfavourable, participants are allowed a further 12 hours’ observation for cervical ripening. Active labour is initiated by amniotomy at cervical scores of ≥6. The primary outcome is the rate of change in the cervical score, and secondary outcomes include active labour within 24 hours of induction, vaginal delivery, time-to-delivery interval and uterine hyperstimulation. All analyses will be intention-to-treat. The data generated in this trial may guide a change in practice towards mechanical labour induction if this proves efficient and safer for women attempting TOLAC compared with PGE2, to improve labour management in this high-risk population.Ethics and dissemination Ethical approval is granted by the Domain Specific Review Board (Domain D) of the National Healthcare Group, Singapore. All adverse events will be reported within 24 hours of notification for assessment of causality. Data will be published and will be available for future meta-analyses.Trial registration number NCT03471858; Pre-results.